Efficacy of progesterone for moderate to severe traumatic brain injury: a meta-analysis of randomized clinical trials - Lin, Chao (Sci Rep, 2015)
Progesterone has been shown to have neuroprotective effects in multiple animal models of brain injury, whereas the efficacy and safety in patients with traumatic brain injury (TBI) remains contentious. Here, a total of seven randomized controlled trials (RCTs) with 2492 participants were included to perform this meta-analysis. Compared with placebo, there was no significant decrease to be found in the rate of death or vegetative state for patients with acute TBI (RR = 0.88, 95%CI = 0.70, 1.09, p = 0.24). Furthermore, progesterone was not associated with good recovery in comparison with placebo (RR = 1.00, 95%CI = 0.88, 1.14, p = 0.95). Together, our study suggested that progesterone did not improve outcomes over placebo in the treatment of acute TBI.